The efficacy of re-warm-up practices during half-time: A systematic review - González-Devesa, D.; Vaquera, A.; Suárez-Iglesias, D.; Ayán-Pérez, C. (Medicina, 2021)
Background and Objectives: The passive nature of rest breaks in sport could reduce athletes` performance and even increase their risk of injury. Re-warm-up activities could help avoid these problems, but there is a lack of research on their efficacy. This systematic review aimed at analyzing the results of those randomized controlled trials (RCTs) that provided information on the effects of re-warm-up strategies. Materials and Methods: Four electronic databases (Web of Science, Scopus, PubMed, and SPORTDiscus) were searched from their inception to January 2021, for RCTs on the effects of re-warm-up activities on sports performance. Interventions had to be implemented just after an exercise period or sports competition. Studies that proposed activities that were difficult to replicate in the sport context or performed in a hot environment were excluded. Data were synthesized following PRISMA guidelines, while the risk of bias was assessed following the recommendations of the Cochrane Collaboration. Results: A total of 14 studies (178 participants) reporting data on acute or short-term effects were analyzed. The main outcomes were grouped into four broad areas: physiological measures, conditional abilities, perceptual skills, and sport efficiency measures. The results obtained indicated that passive rest decreases physiological function in athletes, while re-warm-up activities could help to improve athletes` conditional abilities and sporting efficiency, despite showing higher fatigue levels in comparison with passive rest. The re-warm-up exercise showed to be more effective than passive rest to improve match activities and passing ability. Conclusions: Performing re-warm-up activities is a valuable strategy to avoid reducing sports performance during prolonged breaks. However, given that the methodological quality of the studies was not high, these relationships need to be further explored in official or simulated competitions.